(untitled) (Advancements in Homeopathic Research, 2025)
Dengue fever, a mosquito-borne viral infection, poses significant health challenges worldwide. This case report highlights the effectiveness of individualized homoeopathic treatment in managing dengue fever symptoms, focusing on symptomatic relief and recovery. Dengue fever is an outbreak prone viral disease and is reemerging global health problem. Dengue fever is an acute febrile illness lasting 2-7 days but, in few cases, may progress to critical phase of plasma leakage. Dengue has been identified as one of the 18 neglected tropical disease (NTD’S) by WHO. Peak incidence of dengue fever is observed from July to Nov. According to WHO, about 50-100 million new dengue infections are estimated to occur yearly in more than 100 endemic countries. Homoeopathy is a complementary and alternative system of medicine which is bases on the principle” Similia Similibus Curenture” which means Let like to be Cured by likes. It is a Holistic system which treats the Individuals on the basis of their Individuality. It is second largest treatment in the world (WHO). In Homoeopathy we have many medicines that helps in the treatment of Dengue fever.